2014
DOI: 10.1121/1.4870704
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and analysis of radiated sound from a low speed fan with a large tip gap

Abstract: The wake flow field and radiated sound from a low speed axial fan is studied experimentally. The fan geometry uses controlled diffusion blades and is designed with a low aspect ratio (0.9). The fan is installed with a large tip gap, approximately 10% of the blade span. The radiated sound field is analyzed using a known trailing edge noise formulation. First, the model is compared to an experiment of a single airfoil in a wind tunnel to assess the predictive capabilities. Second, measurements of the fan are mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…1 In recent years, beside the research reported in Jacob et al. 1 that addresses the tip leakage flow of an isolated non-rotating airfoil, most studies are concerned with tip leakage noise in fans: several authors studied low speed fans, 2 fans near surge conditions, 3 rotating instabilities, 4 or fans with tip/casing treatments. 4 In fact, few papers are concerned with tip flows of isolated non-rotating blades, and since the experiments of Jacob et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In recent years, beside the research reported in Jacob et al. 1 that addresses the tip leakage flow of an isolated non-rotating airfoil, most studies are concerned with tip leakage noise in fans: several authors studied low speed fans, 2 fans near surge conditions, 3 rotating instabilities, 4 or fans with tip/casing treatments. 4 In fact, few papers are concerned with tip flows of isolated non-rotating blades, and since the experiments of Jacob et al.…”
Section: Introductionmentioning
confidence: 99%
“…They are not only the cause of aerodynamic losses but are also suspected to be efficient sound sources. For all these reasons, rotor tip clearance flows have been a subject of interest in turbomachinery and aeroacoustic research for a long time as discussed in Jacob et al 1 In recent years, beside the research reported in Jacob et al 1 that addresses the tip leakage flow of an isolated non-rotating airfoil, most studies are concerned with tip leakage noise in fans: several authors studied low speed fans, 2 fans near surge conditions, 3 rotating instabilities, 4 or fans with tip/casing treatments. 4 In fact, few papers are concerned with tip flows of isolated non-rotating blades, and since the experiments of Jacob et al 1 and related computations, there have been no further studies in such academic configurations.…”
Section: Introductionmentioning
confidence: 99%